2015
DOI: 10.1530/rep-15-0007
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism of rs6505162 in the MIR423 coding region and recurrent pregnancy loss

et al.

Abstract: Although the relationship between polymorphisms in microRNAs (miRNAs) and recurrent pregnancy loss (RPL) has been studied, there is very little data available in the literature. In the present study, we scanned 55 potentially functional polymorphisms in the miRNA coding region in Chinese women with unexplained RPL (URPL; no. 2011-10). The rs6505162 COA in the MIR423 coding region was found to be significantly associated with the occurrence of human URPL. The rare A allele contributed to an increase in the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…However, in our study, we did not find a statistically significant association between miR-423 genotypes and RPL risk. Notably, a recent study in the Han Chinese population also failed to identify an association between the miR-423 genotypes and RPL risk; however, the study found an association between miR-423 alleles and RPL, with functional evidence showing that the minor A allele contributed to an increased expression of mature miR-423 [7]. An explanation for the different results may be related to the different allele frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, we did not find a statistically significant association between miR-423 genotypes and RPL risk. Notably, a recent study in the Han Chinese population also failed to identify an association between the miR-423 genotypes and RPL risk; however, the study found an association between miR-423 alleles and RPL, with functional evidence showing that the minor A allele contributed to an increased expression of mature miR-423 [7]. An explanation for the different results may be related to the different allele frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported an association between two pre-miRNA polymorphisms (miR-196a2 and miR-499) and the occurrence of RPL in Korean females [9], which was supported in Iranian women [6]. The most recent study identified a polymorphism in the coding region of miR-423 contributing to an increase in the expression of mature miR-423 associated with RPL in the Han Chinese population [7]. Several miRNAs that are considered important during pregnancy were chosen for this study because of their elevated expression ( miR-27a ), decreased expression in the endometrium and in trophoblasts ( miR-423 ), lower expression during endometriosis ( miR-449b ), and involvement in pregnancy loss via the p53 network ( miR-605 ) [1013].…”
Section: Introductionmentioning
confidence: 96%
“…To our knowledge, our study provides the first piece of evidence that links the functional SNPs in pre‐miR‐323b to RPL susceptibility, although increasing evidences indicated that SNPs in miRNAs were identified to have a great relationship with diseases (Hu et al, ; Jazdzewski et al, ; Saunders et al, ; Su et al, ). Here, we had identified two variant alleles in pre‐miR‐323b that led to the altered production of miR‐323b , which was supposed to be associated with an increased risk for RPL in Han–Chinese population.…”
Section: Discussionmentioning
confidence: 86%
“…(35) In the polymorphism of pre-MIR423 rs6505162, genetic mutations, C to A transition, inhibited the function of HEC-1b cell proliferation and migratory. (36) The abduction of EndMT progression accelerating cell proliferation and migratory capacity was caused by KD serum in endothelial cells, which could be one of the pathogenesis in KD. (14) On the basis of the series of articles above, there is a clear connection between miRNA-423 and coronary artery and coronary collateral.…”
Section: Discussionmentioning
confidence: 99%